HIGHER EDUCATION IS THE ROAD TO THE DEVELOPMENT OF THE COUNTRY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the role and importance of higher education in the development of the country. The social contribution of higher education, its impact on the economic and scientific spheres, its role in highly qualified production and its contribution to innovative development are highlighted, and the current state of production and adjustment is also discussed. The article puts forward the idea of developing higher education as a strategic factor of development.